Techers' Beliefs and Practices on Assessment at SMA N 2 Salatiga in Academic Year 2016/2017 (A Case Study at SMA N 2 Salatiga) - HIDAYAT, MANSUR; , PROF. ENDANG FAUZIATI; , MAULY HALWAT HIKMAT, Ph.D (2017)
Hidayat Mansur, Teachers' Beliefs and Practices on Assessment at SMA N 2 Salatiga in Academic Year 2016/2017 (A Case Study at SMA N 2 Salatiga). Thesis. Master of Language Studies. Graduate Program. Muhammadiyah University of Surakarta. 2017 This research was a case study of English teachers' beliefs and classroom practices at SMA N 2 Salatiga. The objectives of this study were (1) to explore teachers' beliefs on assessment in English teaching, (2) to explore the discrepancy between teachers' beliefs and practices, (3) to explore the assessment reflected in the classroom, and (4) to explore and analyze factors that influence teachers' beliefs and their classroom practices. The type of the research was qualitative research with case study. It was an investigation of a single case or collective case to capture the complexity of objects of the study. The object of the study was teachers' beliefs on assessment at SMA N 2 Salatiga. The subjects of the study were four English teachers consisting of two male and two female teachers. The data sources used in this study were classroom observation, open ended questionnaire, transcript of interview and document. The techniques of collecting data used were open-ended questionnaire, semi-structured interview, classroom observation and document analysis taken from informants. The data validity used was data triangulation to gain accountable information through a variety of sources. Then the researcher used Miles and Hubberman's Model (1993) to analyze the data. The result of this study showed that most of teachers' beliefs were consistent with their classroom practices such as beliefs on assessment, beliefs on cognitive assessment and beliefs on psychomotor assessment. On the other hand, researcher still found one discrepancy namely teachers' beliefs on affective assessment. The factors shaped teachers' beliefs were experience as language learner, training, personal factor and teaching experience. Keyword: Teachers; Beliefs, Assessment, Practices.